PENERAPAN AKUNTANSI MANAJEMEN SEBAGAI VARIABEL MEDIASI PENGARUH PERSEPSI DAN PENGETAHUAN PELAKU USAHA KECIL DAN MENENGAH (UKM) TERHADAP KINERJA UKM - Surenggono .; Siti Djamilah (UNEJ e-Proceeding)
This study aims to analyze the causes and effects of the implementation of management accounting. The cause of the lack of implementation of management accounting allegedly because of the low perception and knowledge of small and medium enterprises. The study also examined the effect of the application of accounting management on the performance of SMEs. This study’s population is managers or owners of SMEs in Surabaya. The sampling technique is random. The analysis technique used to test the hypothesis is structural equation modeling.  The results of a due diligence questionnaire showed a valid and reliable. The results showed perceptions and experiences of SMEs using accounting information significantly influence the application of accounting manajamen, while accounting knowledge no significant effect on the application of management accounting. The results also showed that the application of management accounting significant effect on the performance of Small and Medium Enterprises.